Strain Field Associated With a Component of Divergent Motion Along the Southern Dead Sea Fault: Insights From Magnetic Fabrics. Issue 1 (29th January 2019) - Issachar, R.; Levi, T.; Marco, S.; Weinberger, R.
Abstract: In order to reconstruct the strain field along the southern segment of the Dead Sea Fault (DSF) plate boundary, we analyzed the magnetic fabrics of carbonate rocks, outcropping along it. The magnetic fabrics provide a microstructural indicator that help to approximate the principal strain directions in the rocks. Our analysis includes ~900 cores from 58 sampling localities, along ~400 km of the southern DSF. We measured the magnetic fabrics of (1) pure calcite‐bearing limestones that consist diamagnetic fabrics and (2) chalks with composite fabrics, which we further separated into diamagnetic and paramagnetic subfabrics, using measurements of Anisotropy of Magnetic Susceptibility at low temperatures. The results show that 87% of the diamagnetic fabrics and subfabrics are of tectonic origin. The orientations of the maximum Anisotropy of Magnetic Susceptibility axes ( K 3 axes) approximately align with the maximum horizontal shortening directions along the southern segment of the DSF, differ from the remote stress direction, and are largely parallel to the main trace of the DSF. This parallelism is not related to local variations in the geometry of the faults. We suggest that the deflection of the maximum horizontal shortening parallel to the transform plate boundary is a kinematic consequence of the Sinai‐Arabia relative plate motion, which expresses a component of divergence along the southern segment of the DSF. We conclude that magnetic fabrics of carbonate rocks are sensitive and reliable microstructural indicators for determination of the strain field along major fault systems. Key Points: Magnetic fabrics of carbonate rocks are sensitive strain indicators, suitable for strain field determination along major faults Diamagnetic fabrics of carbonate rocks indicate maximum horizontal shortening parallel to the southern segment of the Dead Sea Fault (DSF) The strain field close to the DSF is local, with a component of divergence